Contemporary drivers of global tourism: Evidence from terrorism and peace factors - Simplice Asongu; Joseph Nnanna; Nicholas Biekpe; Paul N. Acha-Anyi (African Governance and Development Institute (AGDI), 2018)
This study examines the effect of terrorism and peace on tourist destination arrivals using a panel of 163 countries with data for the period 2010 to 2015. The empirical evidence is based on Generalised Method of Moments and Negative Binomial (NB) regressions. Our best estimators are from NB regressions from which the following main findings are established. First, political instability, violent demonstrations and number of homicides negatively affect tourist arrivals while the number of incarcerations positively influences the outcome variable. Second the effects from military expenditure, "armed service personnel" and "security officers and polices" are not positively significant. Managerial implications are discussed.
Keywords: D74; Z32; Z38; 330; Terrorism; Peace; Tourism; Generalised Method of Moments; Negative Binomial Regressions; Military expenditure; Armed service personnel; Security officers and polices; Drivers and Panel data